1991
DOI: 10.1093/mutage/6.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic formation, synthesis and genotoxicity of the N-hydroxy derivative of the food mutagen 2-amino-1-methyl–6-phenylimidazo (4, 5–b) pyridine (PhIP)

Abstract: Hepatic microsomes from rats pretreated with PCB were found to metabolize the food mutagen 2-amino-1-methyl-6-phenylimidazo(4,5-b)pyridine (PhIP) to two major metabolites, one of which was identified as the N-hydroxy derivative, 2-hydroxy-amino-1-methyl-6-phenylimidazo(4,5-b)pyridine (N-OH-PhIP). This identification was based on mass spectral (MS), UV and HPLC data by comparison with N-OH-PhIP prepared by chemical synthesis, as well as the specific activity of the compound in the Ames Salmonella test. Syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 0 publications
3
24
0
Order By: Relevance
“…2-hydroxyamino-1-methyl-6-phenylimidazo [4,5-b]pyridine (N-hydroxylamino-PhIP) was prepared as described previously, by diazotization of PhIP and reaction with sodium nitrite followed by catalytic reduction of the nitro derivative thus obtained with Pd/C to the Nhydroxylamine. [32] The hydroxylamine was acetylated as described previously to afford Nacetoxy-PhIP. [14] Given the expected instability of N-acetoxy-PhIP, it was used without any further purification.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-hydroxyamino-1-methyl-6-phenylimidazo [4,5-b]pyridine (N-hydroxylamino-PhIP) was prepared as described previously, by diazotization of PhIP and reaction with sodium nitrite followed by catalytic reduction of the nitro derivative thus obtained with Pd/C to the Nhydroxylamine. [32] The hydroxylamine was acetylated as described previously to afford Nacetoxy-PhIP. [14] Given the expected instability of N-acetoxy-PhIP, it was used without any further purification.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…32 P-Postlabelling has been the most widely used method for the detection of PhIP-DNA adducts in animal and human tissues offering the advantage that only small amounts of DNA are required for analysis. The development of electrospray ionization (ESI) has permitted the coupling of liquid chromatography (LC) to mass spectrometry (MS), which has been used for the detection of numerous DNA adducts [26].…”
Section: Introductionmentioning
confidence: 99%
“…Most HAs are not mutagenic/carcinogenic in their native form but acquire the capability of forming DNA adducts after metabolic activation [117][118][119]. The major activation pathway of HAs involves phase I N-hydroxylation followed by phase II esterification, both of which take place at the exocyclic amino group.…”
Section: Bioavailability and Bioactivationmentioning
confidence: 99%
“…Of these AIAs, PhIP is the most abundant (0.56 -69.2 ng/g) in well-done meat (1) and is also present in cigarette smoke condensate (16.4 ng per cigarette), wine (14.1 Ϯ 6.18 ng/L), and beer (30.4 Ϯ 16.4 ng/L) (2,3). Although PhIP is the least active AIA in the Ames Salmonella mutagenesis assay, it is the most mutagenic AIA in mammalian cell mutagenesis assays (4,5). Studies in rats have shown that PhIP induces cancers in the colon, mammary gland, and prostate (6 -8).…”
mentioning
confidence: 99%